Pengembangan Buku Kecil (Mini Book) Untuk Meningkatkan Berpikir Kronologis Siswa Kelas X SMAN 3 Pariaman - Abdul Rahman; Zafri Zafri (Jurusan Sejarah FIS UNP, 2021)
The purpose of this study is to develop a teaching material that can improve students' chronological thinking in history learning, teaching materials here can be categorized as printed teaching materials with small sizes in the form of books or also called mini books. In this study, research uses R & D (Research and Development) or what is called research and development, which in this R & D research uses the ADDIE procedure. The result of this research is to create an additional teaching material in the form of a small book (Mini Book) in which there is a material on historical events and most importantly the existence of a chronological table that directs students to think chronologically in history. At the analysis stage, which is related to the needs analysis and character analysis of students, the design stage discusses how to make a small book (Mini Book) and the use of a small book (Mini Book), the development stage talks about product development. Assessment in terms of material gets an average score of 3.70 and can be categorized as very feasible with a percentage result of 92.64% very feasible category. The assessment of the mini book (Mini Book) gets an average score of 3.62 and can be categorized as very feasible with a percentage of 90.62% in the very feasible category. Keywords: Chronological Thinking, Teaching Materials, Mini Book.